Modelled impacts of mitigation measures on greenhouse gas emissions from Finnish agriculture up to 2020 - Regina, Kristiina; Lehtonen, Heikki; Nousiainen, Jouni; Esala, Martti (MTT Agrifood Research Finland, 2009)
Ennusteita kasvihuonekaasupäästöjen kehityksestä voidaan käyttää apuna ilmastonmuutoksen hillintätoimien suunnittelussa. Jos yksittäisten hillintätoimien vaikutuksista päästöihin on olemassa arvioita, voidaan hillintään varattuja resursseja suunnata vaikutukseltaan tehokkaimpiin politiikkatoimiin. Tässä tarkastelussa verrataan kahta kehitysuraa Suomen maatalouden päästöille vuoteen 2020 mennessä: perusskenaario ilman ilmastonmuutoksen hillintään tähtääviä toimia (Skenaario 1) ja politiikkaskenaario (Skenaario 2). Valitut politiikkatoimet olivat 1) peltopinta-alan säilyttäminen nykytasolla, 2) eloperäisten maiden osuuden pienentäminen, 3) nurmen viljelyn lisääminen eloperäisillä mailla ja 4) biokaasutuotannon lisääminen maatiloilla. Skenaario 1 ennusti maatalouden metaani- ja dityppioksidipäästöjen laskevan 2,3 % aikavälillä 2005 2020, kun taas Skenaariossa 2 päästöt vähenisivät 11,5 % hillintätoimien ansiosta. Tutkimuksessa tarkastelluista keinoista eloperäisten maiden viljelyyn kohdistetut toimet vaikuttavat olevan ilmastonmuutoksen hillinnässä kaikkein tehokkaimpia.

Emission scenarios based on integrated quantitative modelling are a valuable tool in planning strategies for greenhouse gas mitigation. By estimating the potential of individual mitigation measures to reduce greenhouse gas emissions, resources can be targeted to the most promising policy measures. This paper reports two agricultural emission scenarios for Finland up to year 2020, one baseline scenario (Scenario 1) based on the projected agricultural production levels determined by markets and agricultural policy and one with selected mitigation measures included (Scenario 2). Measures selected for the analysis consisted of 1) keeping agricultural area at the current level, 2) decreasing the proportion of organic soils, 3) increasing the proportion of grass cultivation on organic soils and 4) supporting biogas production on farms. Starting from 2005, the emissions of nitrous oxide and methane from agriculture would decrease 2.3% in Scenario 1 by 2020 whereas the respective decrease would be 11.5% in Scenario 2. According to the results, mitigation measures targeted to cultivation of organic soils have the largest potential to reduce the emissions. Such measures would include reducing the area of cultivated organic soils and increasing the proportion of perennial crops on the remaining area.
Keywords: Ys; maatalouden sektorimalli; skenaariot; mallinnus; metaani; typpioksidi; kasvihuonepäästöt; Greenhouse gas emissions; emission projections; integrated modelling; methane; nitrous oxide; agricultural policy; mitigation; agricultural sector modelling